Customer Experience Model in the B2B Digital Ecosystem to Enhance Customer Satisfaction - Fitri Lestari; Agus Rahayu; Heny Hendrayati; Rais Iqbal Rabiul Awal (Dinasti International Journal of Education Management And Social Science, 2025)
Purpose - This article aims to open the black box of the relationship between customer experience and customer satisfaction. The authors also take a detailed approach to the concept of customer experience analysis with dimensions: basic service experience (BSE), focus on results (FR),Design/methodology/approach- A total sample of 158 participants of the MSME’s Level Up of the West Java Provincial Office of Cooperatives and Small Businesses, Garut District was collected through google forms from October 1 to November 30, 2024. Data were analyzed using partial least squares structural equation modeling. (PLS-SEM).Findings- The results suggest that the customer experience dimension is the foundation of commercial success (i.e. customer satisfaction) for GoBiz in a business-to-business (B2B) environment. Therefore, the most innovative GoBiz must not only pay attention to providing services in accordance with customer agreements but also go beyond that; thus, these companies must understand customer needs to be able to offer a unique experience. Therefore, these companies must design experiences that go beyond purely technical delivery services.Originality/value - While previous work has linked customer experience to customer satisfaction, there is still little work that does so specifically in a trending industry such as GoBiz and even less in a B2B environment. In addition, this work analyzes a more detailed customer experience.